EVALUATE MULTI VARIABLE EXPRESSIONS

To evaluate a multi variable expression, replace the variables by the given values and simplify using order of operations or PEMDAS.

PEMDAS is the rule that can be used to simplify or evaluate complicated numerical expressions with more than one binary operation.

----> Parentheses

----> Exponent 

M ----> Multiply

----> Divide

----> Add

----> Subtract

Important Notes :

1. In a particular simplification, if you have both multiplication and division, do the operations one by one in the order from left to right.

2. Division does not always come before multiplication. We have to do one by one in the order from left to right.

Evaluate the following expressions using the given values of the variables.

Example 1 :

÷ 2 + x, use x = 1 and y = 2

Solution :

= 4 + 1

= 5

Example 2 :

x + y + y; use x = 9 and y = 10

Solution :

  =  x + y + y

Substitute x = 9 and y = 10.

  =  9 + 10 + 10

  = 29

Example 3 :

 z(x + y); use x = 6, y = 8 and z = 6

Solution :

  =  z(x + y)

Substitute y = 8 and z = 6.

  =  6(6 + 8)

  =  6(14)

  =  84

Example 4 :

(y + x) ÷ 2 + x; use x = 1 and y = 1

Solution :

  =  (y + x) ÷ 2 + x

Substitute x = 1 and y = 1.

=  (1 + 1) ÷ 2 + 1

=  2 ÷ 2 + 1

  =  1 + 1

  =  2

Example 5 :

z − (y ÷ 3 - 1); use y = 3 and z = 7

Solution :

  =  z - (y ÷ 3 - 1)

Substitute y = 3 and z = 7.

=  7 - (3 ÷ 3 - 1)

=  7 - (1 - 1)

=  7 - 0

=  7

Example 6 :

 p - (9 - (m + q)); use m = 4, p = 5 and q = 3

Solution :

  =   p - (9 - (m + q))

Substitute m = 4, p = 5, and q = 3.

=  5 - (9 - (4 + 3))

=  5 - (9 - 7)

=  5 - 2

=  3

Example 7 :

y - (4 - x - y ÷ 2); use x = 3 and y = 2

Solution :

=  y - (4 - x - y ÷ 2)

Substitute x = 3 and y = 2.

 =  2 - (4 - 3 - 2 ÷ 2)

 =  2 - (4 - 3 - 1)

 =  2 - (4 - 4)

 =  2 - 0

=  2

Example 8 :

y ÷ 5 + 1 + x ÷ 6; use x = 6 and y = 5

Solution :

  =    y ÷ 5 + 1 + x ÷ 6

Substitute x = 6 and y = 5.

 =  5 ÷ 5 + 1 + 6 ÷ 6

 =  1 + 1 + 1

=  3

Example 9 :

p - (9 - (m + q)); use m = 4, p = 5, and q = 3

Solution :

=   p - 9 - (m + q))

Substitute m = 4, p = 5 and q = 3.

 =  5 - (9 - (4 + 3))

=  5 - (9 - 7)

=  5  - 2

=  3

Example 10 :

6q + m - m; use m = 8 and q = 3 

Solution :

=  6q + m - m

Substitute m = 8 and q = 3.

 =  6(3)  + 8 - 8

=  18 + 0

=  18

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Simplifying Algebraic Expressions with Fractional Coefficients

    May 17, 24 08:12 AM

    Simplifying Algebraic Expressions with Fractional Coefficients

    Read More

  2. The Mean Value Theorem Worksheet

    May 14, 24 08:53 AM

    tutoring.png
    The Mean Value Theorem Worksheet

    Read More

  3. Mean Value Theorem

    May 14, 24 02:48 AM

    meanvaluetheorem.png
    Mean Value Theorem

    Read More